Synergistic effect of zirconia oxygen vacancies and Cu nanoparticles on catalytic conversion of CO2 to CO at low temperatures - Parisa Ebrahimi (14152392) (2024)
Converting carbon dioxide into valuable chemicals requires suitable catalysts to perform efficiently under severe reaction conditions. Developing suitable supported copper catalysts can potentially improve catalytic performance for CO2 reduction by interacting with copper active components. Herein, we investigate Cu/ZrO2 catalysts, synthesized by wet-impregnation (WI) method with various copper contents, for the reverse water-gas shift (RWGS) reaction. It is anticipated that metal-support interaction, surface defects, and oxygen vacancies in oxide catalysts play critical roles in defining catalytic activity. To understand this, various ZrO2-supported catalysts with different crystallite sizes were prepared by altering the calcination temperature and assessing their catalytic performance. The results showed that 2 wt%Cu/ZrO2 catalyst calcined at 800 °C had the highest CO2 conversion to CO of ∼37 % at 600 °C, with less than 0.25 % coke formation. Kinetics studies showed that the redox model agreed better with experimental data when considering equilibrium conditions. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2024.01.193